Peculiarities of Proceedings in Cases on Imposition of Sanctions for Recovery of Assets Belonging to an Individual or Legal Entity to the State Revenue - Duliba, Yevheniia; Matviichuk, Andrii; Masnyi , Mykhailo (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
To protect the national interests, national security, sovereignty and territorial integrity of Ukraine, counteract terrorist activities, as well as prevent violations and restore the violated rights, freedoms and legitimate interests of Ukrainian citizens, society and the state, the Law of Ukraine No. 1644-VII ‘On Sanctions’ dated 14 August 2014 established the legal framework, grounds and principles for the application of special economic and other restrictive measures - sanctions.  The Law of Ukraine No. 2257-IX dated 12 May 2022 ‘On Amendments to Certain Legislative Acts of Ukraine on Improving the Effectiveness of Sanctions Related to Assets of Individuals’ supplemented the list of types of sanctions with such type as recovery of assets belonging to an individual or legal entity, as well as assets in respect of which such a person may directly or indirectly (through other individuals or legal entities) perform actions identical in content to the exercise of the right to dispose of them, and provides for a special procedure for proceedings in cases of application of these sanctions.The article deals with the peculiarities of proceedings in cases involving the application of sanctions for the recovery of assets belonging to an individual or legal entity, as well as assets in respect of which such a person may directly or indirectly (through other individuals or legal entities) perform actions identical in content to the exercise of the right to dispose of them. The exceptional nature, as well as the purpose, conditions and grounds for applying these sanctions, are disclosed.Based on the analysis of the decisions made by the High Anti-Corruption Court in 2022-2023 and the first half of 2024, the author highlighted peculiarities of proceedings in cases of sanctions for the recovery of acts into the state revenue, which include: the conduct of proceedings in administrative proceedings and the existence of a special procedure for such proceedings, the presence of a plaintiff and a defendant with a special status, the procedure for notifying defendants and other participants of the opening and consideration of the case, as well as the sending and delivery of a court decision, the terms of appeal, etc. Attention is drawn to the persons who may be defendants in this category of cases, the difficulty of establishing the full identification data of sanctioned persons, as well as the types of assets that may be subject to sanctions, the derogation from the 30-day statutory period for consideration of the case, and the peculiarities of court decision-making.